MSMES IN ISLAMIC ECONOMIC PERSPECTIVE - Ummah Ummah (IJED: International Journal of Economy Development Research, 2023)
Resilience of double role of housewife as a perpetrator of MSMEs in the Islamic Emergency Perspective, by referring to the theory of four resolience pages of Coulson. The main purpose of this study is to understand how housewives running micro, small, and medium enterprises (UMKM) overcome their double role challenges, as well as how the application of Islamic economic values can support their resilience. This research is important because it provides insight into the mechanism used by housewives to manage pressure from double responsibility, and how the values of Islamic economy can be an effective tool to strengthen their resilience. It is relevant to provide support to the UMKM actors in overcoming the economic and social difficulties faced. The method used is qualitative method with participant observation approach. The results showed that the housewife of MSME Jamu Day Se experienced four resolience stages. In the early stages, they feel overwhelmed by dual roasting pressure. The phase stage is characterized by changes in view of difficulties as a learning opportunity and seek support. At the recovery stage, they show progress through time management, training, and community empowerment. At the final stage, they experience rapid development with improved skills, business effectiveness, and psychological stability. In addition, the application of the values of Islamic economy, such as patience and tawakal, helps in the early stages; Responsibility and Istiqomah supports at the phase stage; Ikhtiar and Qana'ah play a role in recovery; And generosity and justice facilitate rapid development and positive contribution. These values reinforce the resilience by increasing the commitment, integrity, and social impacts of business.